Pathobiologic Mechanisms of Neurodegeneration in Osteopetrosis Derived From Structural and Functional Analysis of 14 ClC‐7 Mutants. (29th November 2020) - Di Zanni, Eleonora; Palagano, Eleonora; Lagostena, Laura; Strina, Dario; Rehman, Asma; Abinun, Mario; De Somer, Lien; Martire, Baldassarre; Brown, Justin; Kariminejad, Ariana; Balasubramaniam, Shanti; Baynam, Gareth; et al.
ABSTRACT: ClC‐7 is a chloride‐proton antiporter of the CLC protein family. In complex with its accessory protein Ostm‐1, ClC‐7 localizes to lysosomes and to the osteoclasts' ruffled border, where it plays a critical role in acidifying the resorption lacuna during bone resorption. Gene inactivation in mice causes severe osteopetrosis, neurodegeneration, and lysosomal storage disease. Mutations in the human CLCN7 gene are associated with diverse forms of osteopetrosis. The functional evaluation of ClC‐7 variants might be informative with respect to their pathogenicity, but the cellular localization of the protein hampers this analysis. Here we investigated the functional effects of 13 CLCN7 mutations identified in 13 new patients with severe or mild osteopetrosis and a known ADO2 mutation. We mapped the mutated amino acid residues in the homology model of ClC‐7 protein, assessed the lysosomal colocalization of ClC‐7 mutants and Ostm1 through confocal microscopy, and performed patch‐clamp recordings on plasma‐membrane‐targeted mutant ClC‐7. Finally, we analyzed these results together with the patients' clinical features and suggested a correlation between the lack of ClC‐7/Ostm1 in lysosomes and severe neurodegeneration. © 2020 American Society for Bone and Mineral Research (ASBMR).